Investigation of hybrid multilevel DC/AC inverters - Liu, Yu (2008)
In modern technology, power electronics is very important and is now used in a great variety of products, including heat controls, light controls, motor controls, power supplies, vehicle propulsion systems, Flexible AC Transmission Systems (FACTS) and high-voltage dc (HVDC) system.